Corrupting sexual morals and defining pornography - Slavković, Vukan R (Pravni zapisi, 2014)
Summary: A great deal of the difficulty in discussing pornography results from lack of agreement over what is meant by the term. Pornographic material perpetrates images of women as sexual objects and, thus, can victimize women directly and indirectly. „Evil” is said to flow from pornography in two ways. First, it is theorized that there is a direct causal link between violent pornography and violence against women, so that such material can act as a „trigger” to aggression. Second, it is said that pornography contributes in a general way to myths about sexuality and about women that ultimately make violence and degradation more acceptable to society as a whole. Notwithstanding the uncertainties of definition, many believe that material that depicts violence toward women is demonstrably harmful and should be controlled.